Kinerja Pegawai Perempuan: Dampak Kelelahan Emosional dan Konflik Pekerjaan-Keluarga Dimediasi Komitmen Organisasi - Mufida Jenianda Madjid; Sugeng Raharjo (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2026)
Purpose – This study examines the effect of emotional exhaustion and work-family conflict on the performance of women employees, with organisational commitment as a mediating variable. The focus is on women employees at the Central Agency of Statistics of East Kalimantan Province who experience dual demands in work and family roles.Methodology – This quantitative study employed the Partial Least Squares (PLS) approach using SmartPLS 4.0. The sample size was 170 respondents, determined through systematic sampling. Data collection was conducted by distributing questionnaires to women employees within the BPS in East Kalimantan Province.Findings – The findings show that emotional exhaustion does not significantly affect women's employee performance, whereas work-family conflict has a significant negative effect. Emotional exhaustion negatively affects organisational commitment, while work-family conflict does not. Organisational commitment does not mediate the relationships between emotional exhaustion, work-family conflict, and women's employee performance.Originality/Novelty – This study tests an empirical model that integrates emotional exhaustion and work-family conflict as determinants of women employees' performance, with organisational commitment as a mediating variable. Implications – The findings show that although women employees face emotional stress and role conflict, these do not directly reduce their performance, as other factors such as motivation, job satisfaction, and support in the work environment mitigate their effects.